1992
DOI: 10.1152/jappl.1992.73.6.2567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of human dynamic contraction by phonomyography

Abstract: Phonomyogram (PMG, or acoustic myogram) is known to increase with force in isometric contractions. We investigated this relationship for dynamic contractions against different inertias. PMG and surface electromyogram (EMG) from biceps brachii and brachioradialis muscles were simultaneously recorded with the angular acceleration of elbow flexions. These were self-initiated movements (30 degrees) toward a fixed target and performed against two different inertias. PMG and EMG were integrated from the onset of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 0 publications
8
77
1
Order By: Relevance
“…These results confirm earlier studies on human muscles in situ showing positive relationships between PMG and force during voluntary contractions and fatigue, 10,12,15,17,18 and also confirm earlier studies on the human diaphragm, 16 and a small hand muscle, 5,18 showing a good relationship between evoked acoustic responses and evoked twitch force during artificially excited contractions. It thus reinforces a previous conclusion that the amplitude of the phonomyogram can be employed as a noninvasive indicator of force production.…”
Section: Figuresupporting
confidence: 91%
“…These results confirm earlier studies on human muscles in situ showing positive relationships between PMG and force during voluntary contractions and fatigue, 10,12,15,17,18 and also confirm earlier studies on the human diaphragm, 16 and a small hand muscle, 5,18 showing a good relationship between evoked acoustic responses and evoked twitch force during artificially excited contractions. It thus reinforces a previous conclusion that the amplitude of the phonomyogram can be employed as a noninvasive indicator of force production.…”
Section: Figuresupporting
confidence: 91%
“…It has been observed that the amplitude of both LF contraction components [2]- [5] and HF contraction components [1], [6]- [8] of the muscular movement increase with the contraction force. The rationale for inferring the contraction muscle force, from the amplitude of the LF and HF components of the muscle movement, is that the signal constitutes the summation of muscle fibers movement from the recruited muscle motor units and their firing rate.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous measurements of MMG and EMG have been used to examine the dissociation between the electrical and mechanical events (excitationcontraction coupling) that occurs with fatigue (Stokes & Dalton, 1991) and to examine factors related to electromechanical and phonomechanical delay (Petitjean, Maton, & Cnockaert, 1992). In addition, recent studies have examined the MMG amplitude and frequency responses during maximal concentric and eccentric isokinetic muscle actions (Cramer et al, 2002b;2002c;Ebersole et al, 2000;Evetovich et al, 1999), as well as maximal and submaximal cycle ergometry Perry et al, 2001a;2001b;Shinohara, Kouzaki, Yoshihisa, & Fukunaga, 1997;Stout, Housh, Johnson, Evetovich, & Smith, 1997).…”
mentioning
confidence: 99%